The potential of legume cover crops and soil microbes for gold mine tailings revegetation - Triyani Dewi; Sukarjo Sukarjo; C O Handayani; Reginawanti Hindersah; Edwen D Waas; A M Kalay; Hidayatuz Zu’amah (Brawijaya University, 2023)
Mercury (Hg) is commonly utilized in artisanal gold mining on Buru Island; the Hg-contaminated tailing possibly contaminates the agricultural land nearby. In general, tailings contain very low organic carbon and plant nutrients but are high in mercury and have extreme soil acidity. The objective of this study was to observe the growth of various legume cover crops (LCC) and the change of Hg in tailing inoculated with Azotobacter-Trichoderma. The field trial was conducted on Buru Island of Maluku by using a split-plot design with three replications. The main plot was LCC species, composed of Centrosema pubescens (CP), Mucuna sp. (MC), and Crotalaria sp. (CR); the subplots were microbial inoculants composed of two formulations of Azotobacter-Trochoderma inoculants. The results showed that the Mucuna sp. and consortia Azotobacter-Trichoderma (2:1) had the highest survival rate in the tailings and Hg uptake by 8.83 mg kg-1 per plant. Consortia Azotobacter-Trichoderma inoculant with the composition of 2:1 (v:v) was able to increase soil pH, total bacterial population, LCC biomass, and Hg uptake by LCC plants. The highest Hg removal effectivity was observed in the plot treated with Crotalaria sp. and in a plot with Azotobacter-Trichoderma (2:1), which was 34.0% and 33.6%, respectively.